Chronic irreducible dislocation of the proximal interphalangeal joint of the fifth toe: A case report - Vaseenon T. (2014)
Background: Traumatic dislocation of the interphalangeal of the fifth toe is an unusual foot injury. Case presentation. We report the case of a 47-year-old woman who sustained a minor foot injury for more than 30 years, resulting in chronic, irreducible dislocation of the proximal interphalangeal joint of the fifth toe. The affected proximal interphalangeal joint was accessed via a dorsal incision over the unstable interphalangeal joint. It was found that the interposed interphalangeal joint capsule and attenuated lateral collateral ligament were reconstructed, and it was stabilized by temporary insertion of a Kirschner wire. The affected joint was found to be stable, well-positioned and pain-free at the 12-month post-surgical check-up. Conclusion: This unusual presentation of a chronic joint dislocation responded favorably to open reduction, soft tissue reconstruction and restabilization of the affected joint. It is suggested that this approach will provide a good and functional outcome even in cases of very long-standing joint injury. © 2014 Vaseenon et al.; licensee BioMed Central Ltd.